The Islamic Counseling Communication Approach Used by Al-Mukminun Study Group in Addressing Deviant Behavior of Group Members in Bantaeng Sub-District, Bantaeng Regency - Murdifin; Nurhidayat Muhammad Said; Ramsiah Tasruddin (Jurnal Mercusuar, 2022)
This research aims to examine the Islamic Counseling Communication approach used by the Al-Mukminun Taklim Assembly in addressing deviant behaviors among its members in the Bantaeng Sub-District of Bantaeng Regency.This study employs a qualitative descriptive research design conducted in the Bantaeng Sub-District of Bantaeng Regency. The approach used is the Islamic Counseling Guidance approach, along with a Psychological approach. The primary data sources for this research are the informants. The key informant is Abd. Aziz, an Islamic religious counselor who is also the founder and leader of the Al-Mukminun Taklim Assembly. Additional informants include members of the Al-Mukminun Taklim Assembly who exhibit deviant behavior, identified as MS, H, SB, T, I, S, and MA. Secondary data sources include books, internet sources, ebooks, journals, and other complementary materials. Data collection methods involve observation, interviews, and documentation. Data analysis is conducted through three stages: data reduction, data presentation, and conclusion drawing.The results of this research reveal that the Islamic Counseling Guidance approach used by the Al-Mukminun Taklim Assembly in addressing deviant behaviors among its members in the Bantaeng Sub-District of Bantaeng Regency includes: 1. The Behavioristic approach model, 2. The Spiritual Counseling approach model, 3. The Client-Centered approach model.The implications of this research suggest that Islamic religious counselors in Indonesia, especially those in the Al-Mukminun Taklim Assembly of Bantaeng Sub-District, should be more proactive in introducing one of the functions of the taklim assembly, namely the guidance and counseling function. They should also promote the revitalization of counseling or guidance services within the community. Many individuals in society exhibit deviant behavior and psychological issues, often lacking assistance from competent practitioners.